The Pageant of Mutabilitie: Virginia Woolf's Between the Acts and The Faerie Queene. (8th July 2016) - Shackleton, David
Abstract: By drawing a parallel between Miss La Trobe's pageant in Woolf's Between the Acts, and Mutabilitie's pageant in the Mutabilitie Cantos of Spenser's The Faerie Queene, this article elucidates the role played by the aevum —an order of duration that lies between time and eternity—in Woolf's last novel. While the fantasy of an aeviternally permanent nature is a comforting one for Lucy Swithin, this inherently conservative temporal fiction carries a troubling politics, and is deeply problematic from various perspectives. It threatens to petrify exploitative gender, colonial and class relations in a changeless nature, with no prospect of emancipatory historical change. Recognizing Woolf's use of the aevum serves to challenge Brechtian readings of the pageant, and to qualify recent interpretations of Woolf that depict her as holding a revolutionary materialist conception of history, similar to that of Walter Benjamin.